Analysis of Billboard Tax Revenue in Jakarta Province Before and During the Covid 19 Pandemic - Auliya Nur Azizah; Adli (IAEI, 2023)
This study aims to analyze the effectiveness and contribution of advertisement tax revenues for the Province of DKI Jakarta and to find out the strategy of the Regional Government of DKI Jakarta to increase acceptance of effectiveness and contribution. In this study, the sample used was the report on the target and realization of DKI Jakarta Province advertisement tax and the realization of regional original income. Data collection methods used are documentation, literature study, and observation. The data analysis method used in this research is quantitative descriptive analysis which will be processed and analyzed. The results of this research show that in 2018-2022 there was a difference between before and during the Covid-19 pandemic for the effectiveness of advertising tax revenues which increased even during the pandemic, because the target was lowered by the government in 2020 at the beginning of Covid-19, the target value and realization of tax revenues advertising has decreased quite significantly from 2019 before the pandemic. It can be seen from the research results that the effectiveness of advertising tax has an average of 98.09% with effective criteria which always increases every year except in 2022 where it decreases. Meanwhile, the contribution of advertising tax to Original Regional Income did not differ before and during the Covid-19 pandemic. It can be seen from the research results that the contribution of advertisement tax was very low with an average of 2.31%. There is no strategy from the Regional Government to update the old Regional. Regulations from 2011 to 2023 to increase the effectiveness and contribution of advertising tax.